A new species of the genus Thespea Solovyev and four newly recorded species of Limacodidae from India (Lepidoptera: Zygaenoidea) - Singh, Navneet; Ahmad, Jalil; Chandra, Kailash; Solovyev, Alexey V. (Zootaxa, 2021)
Thespea aka, sp. nov., is described as new from Arunachal Pradesh, India. Additionally, four species are recorded for the first time from India: Melinaria pseudorepanda kalawensis (Orhant, 2000) and Parasa julikatis Solovyev & Witt, 2009, recorded in Arunachal Pradesh, and Thosea lutea Heylaerts, 1890 and Mambarona congrua (Walker, 1862), recorded in Great Nicobar Island. Diagnosis and distribution are provided for all taxa listed and the males and their genitalia are illustrated.